2010
DOI: 10.1007/s00244-010-9592-4
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Toxicity in Mid-Continent Great Rivers (USA)

Abstract: As part of the Environmental Monitoring and Assessment Program for Great River Ecosystems (EMAP-GRE), sediment samples were collected from 447 randomly selected littoral sites along the main channels of the Ohio, Missouri, and Upper Mississippi Rivers between 2004 and 2006. Toxicity of these sediment samples was measured using a 7-day Hyalella azteca survival and growth test. Sixty-five sites (14.5%) exhibited lethal toxicity, and 130 sites (29.1%) exhibited decreased growth. In the EMAP-GRE probabilistic samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In that study, sediment samples from multiple near-shore habitats were combined, and therefore, local sediment conditions in dike pools could only be inferred by examining the upstream-downstream pattern in overall toxicity that they documented. Even though Echols et al (2008) suggested a low probability of adverse effects because of contaminants at our dike pool study sites, it is unknown why the conclusions regarding the risk of toxicity in sediments differ among studies (Canfield et al, 1998;Echols et al, 2008;Haring et al, 2011), but it is possible that differences in sampling methodologies and the relative sensitivities of toxicity endpoints may have led to these conflicting results.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In that study, sediment samples from multiple near-shore habitats were combined, and therefore, local sediment conditions in dike pools could only be inferred by examining the upstream-downstream pattern in overall toxicity that they documented. Even though Echols et al (2008) suggested a low probability of adverse effects because of contaminants at our dike pool study sites, it is unknown why the conclusions regarding the risk of toxicity in sediments differ among studies (Canfield et al, 1998;Echols et al, 2008;Haring et al, 2011), but it is possible that differences in sampling methodologies and the relative sensitivities of toxicity endpoints may have led to these conflicting results.…”
Section: Discussionmentioning
confidence: 90%
“…Sediments collected from this tributary have concentrations of many contaminants and sediment‐quality parameters that are one to two orders of magnitude greater than those known in sediments of the Missouri River mainstem (Echols et al , ), and both previous and ongoing research have identified the Blue River as a significant contributor of contaminants, wastewater, nutrient enrichment and a myriad of urban pollutants from many sources (Stern and Stern, ; Wilkison et al , ). Haring et al () also reported a higher frequency of toxicity responses to invertebrates downstream of urban areas on the Lower Missouri River.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations